Geografia da Música: As Interpretações Geográficas de Matogrosso & Mathias na Música “Vingança do Sertão” - NASCIMENTO, Naelton Mendes do (Universidade Federal do Tocantins, 2024)
This work analyzes the song vendetta do sertão, the lyrics are about a “sertanejo” man who portrays the relationship between man and nature and also the possible revenge of nature on society, such as the floods and great droughts that occur within nature, the lyrics also criticize society in relation to inequality and iscrimination against rural people, the “sertanejo”, who are often seen as poor people. Returning to analyze the lyrics of the song it was noticed that many human beings did not notice that so much drought and flood is the reflection of nature on humanity and even so they still continue to infringe the conservation laws, the lyrics of the song expose that the sertão does not it's just the bush, but everything that exists in the sertão like the animals, rivers, mountains, that is, everything that contributes to the landscape in the lyrics described, so the landscape of the sertão in the lyrics is apparent when the singers talk about everything the sun that warms the earth and the great floods for them that is a punishment of the sertão on man.